Water Extract of Portulaca Oleracea Inhibits PEDV Infection-Induced Pyrolysis by Caspase-1/GSDMD - Yu Zhang; Yueyue Liu; Shifa Yang; Bin Yin; Zengcheng Zhao; Zhongli Huang; Jiaqiang Wu; Shuqian Lin; Xin Wang (Current Issues in Molecular Biology, 2023)
Porcine epidemic diarrhea virus (PEDV) belongs to the coronavirus family and the coronavirus genus, causing contact enteric infection in pigs. It is one of the most serious diseases that threatens the pig industry. However, there is currently no specific drug to prevent and treat the disease, indicating that we need to be vigilant about the spread of the disease and the development of anti-PEDV drugs. The dried aerial parts of the plant Portulaca oleracea in the family Portulacaceous, whose decoction can be used to treat acute enteritis, dysentery, diarrhea, and other diseases. This study explored the potential mechanism of water extract of Portulaca oleracea (WEPO) in PEDV-induced pyroptosis in Vero cells. PEDV decreased the viability of Vero cells in a dose- and time-dependent manner, causing cell damage, upregulating the level of intracellular Nlrp3, and inhibiting the level of Gasdermin D (GSDMD) and the activation of Caspase-1. WEPO can inhibit PEDV-induced pyroptosis, reduce the elevation of inflammatory factors caused by infection, and exhibit a dose-dependent effect. Knockdown of Caspase-1 and GSDMD separately can induce the production of the inflammatory factor IL-1β to significantly decrease and increase, respectively. These results suggest that WEPO can inhibit cell pyroptosis caused by PEDV and that the Caspase-1 and GSDMD pathways play an important role in this process.